(untitled) (KONFERENSIYA, 2026)
This article explores the challenges and strategies in translating fantastic toponyms and names in the fantasy world of Game of Thrones, originally created by George R.R. Martin. The translation of fictional place names and character names poses unique difficulties due to their invented nature, rich cultural connotations, and symbolic meanings. This study aims to analyze selected examples of toponyms and names in the original English text and their equivalents in Uzbek and Russian translations, identifying the techniques used by translators. The research applies a comparative and descriptive method, focusing on whether translators prioritized semantic transparency, phonetic fidelity, or cultural adaptation. The findings reveal that most translators tend to preserve the original forms of names to maintain authenticity, while some adapt them for easier comprehension or cultural relevance. This paper concludes that translating fantasy names requires not only linguistic skill but also a deep understanding of the fictional world’s internal logic and cultural depth.